Universal health coverage-Exploring the what, how, and why using realist review. - Aklilu Endalamaw; Tesfaye Setegn Mengistu; Resham B Khatri; Eskinder Wolka; Daniel Erku; Anteneh Zewdie; Yibeltal Assefa (PLOS Global Public Health)
Universal health coverage (UHC) is a critical target in many health system strategies to achieve 'good health and wellbeing'. Evidence on the meaning and scope of UHC and the strategies required to achieve it are needed, as variations in its understanding and implementation have risen. This realist review was conducted to fill the knowledge gap by synthesising evidence on the meaning, components, significance, and strategies of UHC. A review of evidence was conducted based on realist synthesis. We searched PubMed, EMBASE, Scopus, and Web of Science for published materials and websites for grey literature. We have followed some steps: define the scope of the review and develop initial programme theory, search for evidence, data extraction, and synthesise evidence. This review revealed that universal coverage, universal health, universal healthcare, universal access, and insurance coverage are used interchangeably with UHC. It is a legal notion that embodies a human rights-based and collaborative approach to ensure fair and comprehensive health care services. Universal health coverage is relevant for three macro reasons: first, it prevents and reduces the impact of diseases; second, it addresses inequality and promotes equity; and third, it is key for global health security. Various mechanisms are involved to implement UHC, such as health insurance, social health protection, digital financing systems, value-based care, private sectors, civil societies, partnerships, primary health care, and reciprocal health care systems. In conclusion, universal health coverage is a multifaceted concept that various terms can express in different contexts. Universal health coverage is a political and ethical imperative that aims to promote health equity and protect human dignity across different levels of society. It is essential in preventing diseases and crucial to global health security. Practically, UHC is not truly universal, as it does not include all services under its scheme and varies across countries. This requires consistent advocacy, strategic and operational research, and political will to ensure UHC.